2015
DOI: 10.1002/2015jd023523
|View full text |Cite
|
Sign up to set email alerts
|

Identifying robust transport features of the upper tropical troposphere

Abstract: Multimodel ensembles of back trajectories calculated from four different analysis data sets and two different trajectory formulations ("diabatic" and "kinematic") are analyzed to investigate seasonal mean boundary layer-to-"tropopause" (100 hPa) transport in the tropics. Transport paths are separated into two legs: "convective uplift" (boundary layer to detrainment) and "radiative ascent" (detrainment to tropopause). The following three diagnostic measures are used: source location, source-to-tropopause transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 68 publications
4
22
0
Order By: Relevance
“…Bergman et al . [] examined how trajectories differ from these same models in order to isolate robust features of transport to the tropical tropopause. They found that intermodel variations of parcel densities often (though not typically) exceed 50%.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Bergman et al . [] examined how trajectories differ from these same models in order to isolate robust features of transport to the tropical tropopause. They found that intermodel variations of parcel densities often (though not typically) exceed 50%.…”
Section: Resultsmentioning
confidence: 99%
“…These calculations were used by Bergman et al . [] to identify robust features of source distributions for air entering the tropical stratosphere. The comparison between dispersion from the multimodel approach and the other ensemble approaches reveals the impact of wind data uncertainty on trajectory dispersion and, thus, complements the analysis of Bergman et al .…”
Section: Experimental Design Models and Input Datamentioning
confidence: 99%
See 3 more Smart Citations